NITROGÊNIO EM COBERTURA E MOLIBDÊNIO VIA FOLIAR NO FEIJOEIRO EM PLANTIO DIRETO - Silva, Tiago Roque Benetoli da; Tavares, Carolina Amaral; Lemos, Leandro Borges; Soratto, Rogério Seres (REVISTA DE AGRICULTURA, 2020)
NITROGÊNIO EM COBERTURA E MOLIBDÊNIO VIA FOLIAR NO FEIJOEIRO EM PLANTIO DIRETO